The Effect of The Use of DLM (Digital Learning Material) on Social Studies Learning Outcomes of Fifth-Graders - Mahendra, Hatma Heris; Nurani, Riga Zahara (International Conference on Elementary Education, 2020)
Modern learning requires the teachers to become facilitators whose involvements are limited. Teachers can use DLM as an alternative support in learning. This study focuses more on describing the effect of the use of DLM (Digital Learning Material) especially in Social Studies subject for fifth-graders. DLM, or Bahan Ajar Digital in Bahasa, offers several advantages to support the implementation of active and interactive learning. This research uses a quantitative approach using a quasi-experimental method, and the Nonequivalent Control Group Design. It was conducted at SDN Dadaha, Tasikmalaya, with class V C as the control class and class V B as the experimental class. The control class received learning without DLM (Digital Learning Material), while the experimental class received learning with DLM (Digital Learning Material). The analysis of research data shows the Mean Rank or the average rating of the control class was 15.48, lower than that of the experimental class, which is 33.42. The significance value of the result is smaller than the value of Î± (0,000 <0.05) thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It is concluded that the effect of the use of DLM (Digital Learning Material) on the improvement of Social Studies learning outcomes of fifth-graders is evident.